Biphasic effects of autophagy on decompression bubble-induced endothelial injury - Wang, M.; Zhang, K.; Nie, S.; Huang, G.; Yi, H.; He, C.; Buzzacott, Peter; Xu, W. (WILEY, 2019)
Endothelial dysfunction induced by bubbles plays an important role in decompression sickness (DCS), but the mechanism of which has not been clear. The present study was to investigate the role of autophagy in bubble-induced endothelial injury. Human umbilical vein endothelial cells (HUVECs) were treated with bubbles, autophagy markers and endothelial injury indices were determined, and relationship strengths were quantified. Effects of autophagy inhibitor 3-methyladenine (3-MA) were observed. Bubble contact for 1, 5, 10, 20 or 30 minutes induced significant autophagy with increases in LC3-II/I ratio and Beclin-1, and a decrease in P62, which correlated with bubble contact duration. Apoptosis rate, cytochrome C and cleaved caspase-3 increased, and cell viability decreased following bubble contact for 10, 20 or 30 minutes, but not for 1 or 5 minutes. Injuries in HUVECs were correlated with LC3-II/I ratio and partially reversed by 3-MA in 10, 20 or 30 minutes contact, but worsened in 1 or 5 minutes. Bubble pre-conditioning for 1 minutes resulted in increased cell viability and decreased apoptosis rate compared with no pre-conditioning, and 30-minutes pre-conditioning induced opposing changes, all of which were inhibited by 3-MA. In conclusion, autophagy was involved and played a biphasic role in bubble-induced endothelial injury.